Characterization Of Plant Growth Promoting Rhizobacteria (PGPR) From Bamboo - A Napoleon; Agus Hermawan; Muh Bambang Prayitno (Journal of Smart Agriculture and Environmental Technology, 2026)
PGPR (Plant Growth Promoting Rhizobacteria) are root bacteria that trigger plant growth by colonizing a thin soil layer of about 1 mm-2 mm. PGPR can be derived from golden bamboo (Bambusa vulgaris) roots, bamboo roots contain hormones such as auxin, cytokinin and gibberillin which can stimulate root growth and plant development. This study aims to identify the morphological characteristics of PGPR bacteria from bamboo rhizosphere. This research was conducted in June-July 2023 in the experimental garden of ATC (Agrotech Training Center) owned by the Faculty of Agriculture, Sriwijaya University. This study used a simple experimental method to identify the morphological characteristics of bacteria in general. This method is carried out by conducting experiments, namely taking bamboo rhizosphere material and identifying the isolates obtained and then concluding from the experiments that have been carried out by proving the results obtained in accordance with existing research. In this study, there were 5 bacterial isolates successfully grown on Nutrient Agar (NA) media with different colony morphologies. Bacterial morphology found in giant colony isolates of PGPR solution from bamboo rhizosphere has a shape (Irregular and Circular); elevation (flat); edge (Lobate and Undulate); Color (Transparent, Milk White to Yellowish; and cell shape (Streptococcus and Palisade). The results of the identification of bacterial species indicated that the PGPR solution from the bamboo rhizosphere belonged to the Pseudomonas fluorescens and Bacillus polymixa species.